(untitled) (Journal of the College of Basic Education, 2022)
The contrasting effectiveness of the design spaces refers to the creative field, as well as having the aspect of contributing to all the activities decided by the artist-designer. And since the effectiveness of contrast is the focus of the current study, delving into its importance means delving into the essence of the creative activities of interior design, which is a web of relationships and events that depend mainly on contrast in building its multiple systems, including diversity, contrast, and gradation. Contrast should be available in all design activities, as it helps to attract attention and achieve a strong feeling for the recipient.